A Shepherd for the Naïve: Images of Future Government in Huxley, Bradbury, and Forster. (26th August 2015) - Atkinson, Christopher L.
Intellectuals of the 20th century bore witness to society's injustices. They viewed and commented on erosion of rights and humankind's callousness to itself. For example, Huxley's Brave New World and Brave New World Revisited illustrate with contempt a society that had renounced personal individuality and rejected freedom, choosing a drugged totalitarian state set adrift from any sense of morality. Huxley's work is a familiar touchstone, in that it presupposed a world that seems increasingly real to us, even though a faithful portrayal of the future was hardly Huxley's intent. Bradbury's Fahrenheit 451 soberly reminded the world of the wages of intolerance to divergent ideas, in envisioning a government solidifying its hold on power by banishing the spectrum of human emotion in literature and mass media. Forster's ambitious short story "The Machine Stops" countered the naiveté of a positive equal utopia, with a world cruel in its homogenization and dependent on a deified machine for all facets of its existence. In each instance, government is an ominous, questionable character. Technology, in these texts and in today's world, is a foundational element with muddled aims—a rich virtual society on one hand, but frightening levels of assimilation, control, and loss of interpersonal communication and privacy in the crumbling arena of the real on the other. In this article, a future technology-led existence is examined through the lenses of these fictional works.